Ethanol in pancreatic juice after oral and intravenous administration. Issue 12 (December 1990) - Gjørup, I; Dueholm, S; Andersen, B; Burcharth, F
Abstract : Six patients with a drain in the main pancreatic duct were studied. Ethanol was given orally with individually adjusted doses aiming at a blood value of 0.8/1000 (17.6 mmol/l). Concentrations of ethanol in venous blood and pancreatic juice were recorded for three hours. Similar studies were made when ethanol was administered as an intravenous priming dose followed by a maintenance infusion. After orally administered ethanol, pancreatic juice values were higher than those in blood for a short period of time. The relations between median concentrations and time were incongruous curves consistent with a significant treatment by time interaction. Intravenous administration resulted in a similar pattern, but the interaction was not statistically significant. These findings indicate that the human pancreas may secrete ethanol.